2019
DOI: 10.4103/ija.ija_823_18
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and safety of videolaryngoscopy-guided verbal feedback to teach neonatal and infant intubation. A prospective randomised cross over study

Abstract: Background and Aims:Neonatal endotracheal intubation is challenging due to the miniature anatomy, which is distinct from adults and reserves only less oxygen and time before desaturation begins. As a result, teaching neonatal intubation becomes fraught with difficulties. This study aimed to determine the efficacy and safety of videolaryngoscopy-guided verbal feedback compared to conventional laryngoscopy verbal feedback in neonatal and infant intubation.Methods:In this prospective randomised cross over study, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 7 publications
1
18
0
Order By: Relevance
“…Of the 13 eligible studies, nine were excluded as they investigated the use of VL versus DL in simulations using mannequins or focused on the use of VL for intubation, not as a teaching tool. Four studies met all inclusion criteria for this review: two parallel RCT [ 7 , 10 ] and two RCTs with crossover [ 6 , 20 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Of the 13 eligible studies, nine were excluded as they investigated the use of VL versus DL in simulations using mannequins or focused on the use of VL for intubation, not as a teaching tool. Four studies met all inclusion criteria for this review: two parallel RCT [ 7 , 10 ] and two RCTs with crossover [ 6 , 20 ].…”
Section: Resultsmentioning
confidence: 99%
“…Characteristics of included studies are summarized in Appendix 2 2 with extracted data in Table 1 . Four RCTs [ 6 , 7 , 10 , 20 ] met the inclusion criteria for this review, with two using crossover designs [ 6 , 20 ]. All four RCTs were conducted in hospital settings of a neonatal intensive care unit (NICU), labour and delivery ward, or operating room.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Numerous benefits of VL have been reported, and these include improved laryngeal view, visual confirmation of tube placement, high rates of successful rescue after failure of direct laryngoscopy,[ 2 ] reduction in applied force,[ 8 ] a steep learning curve,[ 9 ] improved training of novices,[ 10 11 ] and improved operator ergonomics,[ 12 ] but evidence of benefit is not available for all devices or all circumstances, making clinical decisions and device choice complex. A systematic Cochrane review comparing VL with direct laryngoscopy reported improved glottic view, reduced intubation failure as well as reduced incidence of laryngeal/airway trauma.…”
Section: Discussionmentioning
confidence: 99%
“…Recent literature[ 19 20 ] has studied the superiority of VL over direct laryngoscopy in neonates and infants by novices and found that novices had higher first-attempt success rate and fewer oesophageal intubations with VL as compared to those with direct laryngoscope-guided intubation. Therefore, the performance of KVL, in terms of first-attempt intubation success rate and complications in paediatric tracheal intubation, when used by trainees and novices, is another important premise which warrants future dedicated research.…”
Section: Discussionmentioning
confidence: 99%